Correlation of the SUVmax of FDG-PET and ADC values of diffusion-weighted MR imaging with pathologic prognostic factors in breast carcinoma. Issue 5 (May 2016) - Kitajima, Kazuhiro; Yamano, Toshiko; Fukushima, Kazuhito; Miyoshi, Yasuo; Hirota, Seiichi; Kawanaka, Yusuke; Miya, Mouri; Doi, Hiroshi; Yamakado, Koichiro; Hirota, Shozo
Abstract: Purpose: To correlate both primary lesion maximum standardized uptake values (SUVmax ) of FDG-PET/CT, and apparent diffusion coefficient (ADC) values of diffusion-weighted imaging (DWI) with clinicopathologic prognostic factors in patients with breast carcinoma. Materials and methods: 214 patients with 216 mass-type invasive breast carcinomas underwent whole-body FDG-PET/CT and 3-Tesla breast MRI including DWI before initial therapy. The primary tumor's SUVmax and ADC values were measured using FDG-PET/CT and DWI, respectively. Histologic analysis parameters included tumor size, expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki-67, nuclear grade, histology subtype, and axillary lymph node (LN) metastasis. The relationships among SUVmax, ADC values, and pathologic prognostic factors were evaluated. Results: The mean SUVmax and ADCmean were 5.63 ± 3.79 (range, 1.2–24.17) and 894 ± 204 × 10 −6 mm 2 /s (range, 452–1550 × 10 −6 ), respectively. There was a significant but weak inverse correlation between the SUVmax and ADCmean values (correlation coefficient r = −0.30, p < 0.0001). SUVmax was associated with numerous prognostic factors such as tumor size (p < 0.0001), expression levels of ER (p = 0.00041), PR (p = 0.00028), HER2 (p = 0.00021), and Ki-67 (p < 0.0001), nuclear grade (p < 0.0001), histology subtype (p = 0.00061), axillary LN metastasis (p < 0.0001), and TNM staging (p < 0.0001). Meanwhile, ADCmean value was associated with tumor size (p = 0.013), expression of Ki-67 (p = 0.0010), histology subtype (p = 0.00013), axillary LN metastasis (p = 0.00059), and TNM staging (p = 0.0011). Conclusions: Primary tumor SUVmax on FDG-PET/CT has a stronger relationship with known prognostic parameters and may be a more useful for predicting the prognosis of breast carcinoma than ADC values.